The Penyuluhan Kesehatan Tentang Jajanan Sehat Pada Siswa SD Muhammadiyah Kebagusan - minto aji, tommi maulana; muttaqien, mohammad wildan; hidayat, azam syarif; Putri, Mega Widya (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2024)
Currently, there are still many people who do not care about what they eat, both adults and children. For people, the most important thing about food is good taste, large portions, and the right price. People, especially children, tend to buy food without paying attention to cleanliness. So it often happens that they become victims of unhealthy snacks. This happens because of the lack of knowledge about how to recognize safe snacks. School children's snacks whose health is not guaranteed can cause poisoning, digestive disorders, and if it lasts for a long time will cause poor nutritional status. The method used is counseling held by Muhammadiyah SD Kebagusan. The results of this activity showed an increase in the average value of prior knowledge and after health education. The results of this community service are expected to produce students who have knowledge about healthy snacks. It is hoped that the results of this service will become basic capital in forming clean and healthy living behavior in the school setting, so that a healthy and strong generation is created.